the Nilai Kasih Sayang Ibu Dalam Perspektif Pendidikan Agama Islam Sebagai Fondasi Karakter Anak: Studi Pustaka - Marshela Damayanti; An nisa; Elsa Oktavia; Tariza Apryandi; Alihan Satra (STKIP Subang, 2026)
This study aims to analyze the values of maternal affection in the perspective of Islamic Religious Education and its role as a foundation for children’s character education. This research uses a qualitative approach with a library research method. The data sources consist of primary data in the form of the Qur’an and hadith, and secondary data derived from classical and contemporary Islamic literature, including books of tafsir, hadith, and Islamic education. Data were collected through documentation techniques by identifying, selecting, and classifying relevant literature. The data were analyzed using descriptive qualitative analysis through data reduction, categorization, interpretation, and conclusion drawing. The results show that maternal affection in Islam is not merely an emotional expression, but a concept with theological, moral, and pedagogical dimensions rooted in the value of compassion. The values of maternal affection include gentleness, patience, care, responsibility, and exemplary behavior, which function as effective means in instilling moral values in children. Furthermore, maternal affection plays a strategic role as a foundation for character education by facilitating the internalization of values such as honesty, discipline, responsibility, and social awareness. Therefore, maternal affection becomes a fundamental element in shaping children’s character and contributes to the development of morally upright individuals in accordance with Islamic teachings.